Adherence to blood pressure measurement guidelines in long‐term care facilities: A cross sectional study. (30th March 2018) - Ozone, Sachiko; Sato, Mikiya; Takayashiki, Ayumi; Sakamoto, Naoto; Yoshimoto, Hisashi; Maeno, Tetsuhiro
Abstract: Objective: To assess the extent to which long‐term care facilities in Japan adhere to blood pressure (BP) measurement guidelines. Design: Cross‐sectional, observational survey. Setting: Japan (nationwide). Participants: Geriatric health service facilities that responded to a questionnaire among 701 facilities that provide short‐time daycare rehabilitation services in Japan. Methods: A written questionnaire that asked about types of measurement devices, number of measurements used to obtain an average BP, resting time prior to measurement, and measurement methods when patients' arms were covered with thin (eg, a light shirt) or thick sleeves (eg, a sweater) was administered. Main outcome measure: Proportion of geriatric health service facilities adherent to BP measurement guidelines. Results: The response rate was 63.2% (443/701). Appropriate upper‐arm BP measurement devices were used at 302 facilities (68.2%). The number of measurements was appropriate at 7 facilities (1.6%). Pre‐measurement resting time was appropriate (≥5 minutes) at 205 facilities (46.3%). Of the 302 facilities that used appropriate BP measurement devices, 4 (1.3%) measured BP on a bare arm if it was covered with a thin sleeve, while 266 (88.1%) measured BP over a thin sleeve. When arms were covered with thick sleeves, BP was measured on a bare arm at 127 facilities (42.1%) and over a sleeve at 78 facilities (25.8%). Conclusions: BP measurement guidelines were not necessarily followed by long‐term care service facilities in Japan. Modification of guidelines regarding removing thick sweaters and assessing BP on a visit‐to‐visit basis might be needed. Abstract : In long‐term care facilities in Japan, blood pressure (BP) measurement guidelines were not always followed with regard to device type, number of measurements, and approach to upper body clothing. The proposal of using upper arm devices for BP measurements, removing thick clothing as much as possible for examination, and assessing measurements across visits instead of multiple measurements in succession may be feasible in these settings.